The Use of Positive Language on ELT to Promote Students’ Writing Competence - Amrina Rosyada; Zumrotul Muniroh (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Teachers’ language is one of the important aspects that contributes on students’ competence in any levels. It promotes students’ engagement in the learning process and also effects students’ output of their learning. It doesn’t prevail only on kindergarten students or primary students, but also on higher level such as college or university level. This research is aimed at determining the use of positive language to promote students’ writing competence in university level. The focus of the research is on writing competence where students face terribly writing difficulties. Engaged by the 3rd semester of 41 students of Basic Writing class in English Education Program, the research was measured statistically in a correlational analysis. Findings show that there is a significant correlation between the use of positive language and the result of the students’ writing competence. Most students show that they need positive language applied in their classrooms, so that they would fully participate in the learning process. Further, the students can reach their best results of their learning and gain their highest competence. Instead of vanish, language as a powerful teaching tool would be demanded by all levels of students for centuries.